Stylistics Features in Personal Essay of English Department’s Student - Aang Fatihul Islam; Dian Anik Cahyani; Ika Lusi Kristanti (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2016)
This research focus oh how students apply pragmatylistics in personal essay whereas their background are organization activist who also have good academic achievement. This research apply some theories in analyzing data, namely: stylistics, personal essay and communication. This research used descriptive qualitative method. Beside that this research use two data collection techniques: observation and interview. So that this research describe phenomenon which relate to research problem. Based on the findings, students apply some of stylistics expression which categorize into two: (1) lexical features: pararelism, and rhetorical question, and comparison and (2) figurative language: accumulation, ephipora, hyphopora, personification, accumulation, simile, symbol, metaphor, and antithesis